Reading the meaning of love in world interfaith harmony week's anthem : semiotics of poetry analysis - Wakhyu Arif Pambudi (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2018)
wt,1./ws.c.1